2004
DOI: 10.4049/jimmunol.173.4.2231
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Expression of Chemokine Receptor CXCR1 on Human Effector CD8+ T Cells

Abstract: IL-8 is a potent inflammatory cytokine that induces chemotaxis of neutrophils expressing CXCR1 and CXCR2, thus indicating its involvement in the migration of these cells to inflammatory sites where bacteria proliferate. Presently, we showed that CXCR1+ cells were predominantly found among CD8+ T cells having effector phenotype, and that the expression of CXCR1 was positively correlated with that of perforin, suggesting that CXCR1 is expressed on effector CD8+ T cells. Indeed, human CMV-specific CD8+ T cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 21 publications
3
63
0
Order By: Relevance
“…Our recent study demonstrated that the surface expression of CXCR1 is positively correlated with that of perforin [24]. These findings suggest that the expression of CXCR4 correlates negatively with the expression of CXCR1.…”
Section: Correlation Between the Expression Of Cxcr4mentioning
confidence: 81%
See 1 more Smart Citation
“…Our recent study demonstrated that the surface expression of CXCR1 is positively correlated with that of perforin [24]. These findings suggest that the expression of CXCR4 correlates negatively with the expression of CXCR1.…”
Section: Correlation Between the Expression Of Cxcr4mentioning
confidence: 81%
“…CD27 -CD28 -CD45RA - [7,15,23]. A recent study demonstrated that CXCR1 is expressed on effector and effector/memory CD8 + T cells with phenotypes of CD27 -CD28 -CD45RA +/-and CD27 low CD28 -CD45RA +/-, respectively, and that the expression of CXCR1 correlates with that of perforin [24].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have identified a subset of human CD8 + T cells that express CXCR1, respond to IL-8 and have cytotoxic function [22,23]. Memory CD8 + T cells do not express this receptor [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In uninfected mice the mean percentage of CD27 -cells within the lung CD8 + T-cell population was 11% and upon influenza infection this increased to 20% at day 9 and 29% at day 20 after infection ( Table 1). The increase in the lung at day 9 was possibly due to nonspecific migration of CD8 + CD27 -memory T cells in response to inflammatory mediators produced in inflamed lung [38][39][40] because at this time point nearly Liver 208 Table 2. In a CD27 x CD62L dot plot three subpopulations were identified: R1, CD62L + CD27 + ; R2, CD62L -CD27 + ; R3, CD62L -CD27 -.…”
Section: Cd27 Expression Is Lost After Repetitive Stimulation In Vivomentioning
confidence: 98%